La ciencia política en Uruguay: un desarrollo tardío, intenso y asimétrico - Garcé, Adolfo (Revista de Ciencia Política, 2019)
In Uruguay, social sciences have developed later than in other countries in the region. Political science, as an independent discipline, was only institutionalized at the end of the 1980s when, within the University of the Republic, a specialized institute of research was established and began to offer undergraduate courses in the discipline. It is undeniable that during the 1990’s political science experienced an intensive growth both in the number of students and research activities. At the same time, political scientists started to play an important role in the political analysis and public debate. Nevertheless, currently, Uruguayan political science faces the challenges of correcting some important asymmetries.